2022
DOI: 10.1093/jme/tjac103
|View full text |Cite
|
Sign up to set email alerts
|

Survival and Fecundity of Anopheles stephensi and Anopheles albimanus Mosquitoes (Diptera: Culicidae) After Ingesting Bovine Blood Containing Various Veterinary Systemic Parasiticides

Abstract: Systemic parasiticides in livestock can control zoophilic malaria vectors that contribute to residual malaria transmission. Membrane feeding techniques were used to screen seven systemic parasiticidic drugs currently in veterinary use for livestock and dogs. Drugs were tested in two laboratory strains of zoophilic Anopheles – A. stephensi (South Asian vector) and A. albimanus (Central American vector). To assess the relative potentials of these drugs, the resultant LC-50 for each drug was compared with what is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…aquasalis. The low values determined here are more than suitable to cause a lethal effect on this malaria Neotropical vector even though it is known that much higher maximum concentrations of the drug are presented in the bloodstreams of dogs (45), cats (46), and cattle (47).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…aquasalis. The low values determined here are more than suitable to cause a lethal effect on this malaria Neotropical vector even though it is known that much higher maximum concentrations of the drug are presented in the bloodstreams of dogs (45), cats (46), and cattle (47).…”
Section: Discussionmentioning
confidence: 80%
“…The administration of insecticidal drugs to cattle to reduce malaria has been used and indicated for disease control in eld regions (50). Recently, Fluralaner has been explored for this purpose (47). The authors showed that while Fluralaner signi cantly affected mortality in An.…”
Section: Discussionmentioning
confidence: 99%
“…stephensi LC 50 : 123 ng/ml; An. albimanus LC 50 : 23 ng/ml) [ 36 ]. Conversely, fipronil outperformed fluralaner 100-fold when Ae.…”
Section: Discussionmentioning
confidence: 99%
“…To assess oral toxicity, females were offered a blood meal spiked with fluralaner in an artificial membrane feeding system; 100 mg of technical grade fluralaner was dissolved in DMSO to the concentration of 2 mg/ml. This solution was further diluted in PBS (Sigma-Aldrich, St. Louis, MO) to 2000 ng/ml [ 36 ] to create a stock solution. This fluralaner spiked PBS stock solution was then diluted in defibrinated sheep blood (Carolina Biological Supply Co., Burlington, NC) to concentrations of 10, 30, 50, 70, 300, 400 or 1000 ng/ml.…”
Section: Methodsmentioning
confidence: 99%
“…Mosquito mortality at 7, 14 and 21 days post-treatment was signi cantly higher for those fed on blood samples from individuals treated with IVM compared to the control group, with the highest mosquito mortality observed at day 7. Likewise, the lethal effect of IVM on mosquitoes fed on cattle treated with IVM has been shown in several studies [8, [12][13][14][15]. IVM, when ingested with blood meal, targets the mosquitoes' glutamate-gated chloride ion channel (GluCl) in the muscle and nerve cells to exert neuronal signals that manifest in mosquitoes' paralysis and death [16].…”
Section: Introductionmentioning
confidence: 99%